Actus Reus dan Mens Rea dalam Perspektif Pragmatik: Kajian Linguistik Forensik terhadap Kejahatan Berbahasa - Hamidi, Ahmad (Puitika, 2024)
In criminal law evidence mechanisms, actus reus and mens rea are two elements that must be fulfilled. A person suspected of committing a criminal offense cannot be held criminally liable if the element of mens rea is not found in their actions, even if actus reus is present (in certain crimes, legal liability depends on mens rea). This study aims to demonstrate the relevance between actus reus and mens rea in language-based criminal offenses, presented through a forensic linguistic approach. It highlights the role of linguistics in describing and explaining linguistic phenomena structurally and intentionally within the scope of criminal law evidence. The utterance data for this case study were sourced from cases handled by the Polrestabes Bandung. This study employs three main theories, i.e. presupposition, speech acts, and felicity conditions, with additional relevance theory, conversational implicature, and politeness principles. Based on the findings, it can be concluded that a criminal act (actus reus) that lacks malicious intent (mens rea) but arises from negligence (culpa) does not necessarily meet the criteria for prosecution under Article 45(3) of Law No. 19 of 2016 on Information and Electronic Transactions (ITE), as the act is deemed not to fulfill the element of â€œSetiap Orang yang dengan Sengajaâ€ as stipulated in the article.